2015
DOI: 10.24839/2164-8204.jn20.4.217
|View full text |Cite
|
Sign up to set email alerts
|

The Virtual Destruction of Self-Compassion: Cyberbullying’s Damage to Young Adults

Abstract: There is significant variation in the degree to which various religions systematically condemn same-sex ABSTRACT. The current research investigated whether priming students with a religious message affected their attitudes toward lesbians and gay men. Undergraduate students (N = 145) were randomly assigned to 1 of 3 conditions: participants in a religious-positive condition were primed with a biblical passage containing a loving message (e.g., "love one another, for love comes from God"), participants in a rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Without adaptive cognitive coping strategies to regain mastery or self-esteem in a situation, individuals who are bullied may experience low self-compassion and increased shame. One study on the relationship between cyberbullying experiences and self-compassion in 232 undergraduates found that victimization experiences negatively correlated with three aspects of self-compassion: self-judgment, isolation, and overidentification (Potts & Weidler, 2015). Boulton (2013) used retrospective measures to study the effects of childhood experiences of being bullied on social anxiety in adults, looking at self-blame and style of coping as moderators.…”
Section: A Model Of Bullying and Shamementioning
confidence: 99%
“…Without adaptive cognitive coping strategies to regain mastery or self-esteem in a situation, individuals who are bullied may experience low self-compassion and increased shame. One study on the relationship between cyberbullying experiences and self-compassion in 232 undergraduates found that victimization experiences negatively correlated with three aspects of self-compassion: self-judgment, isolation, and overidentification (Potts & Weidler, 2015). Boulton (2013) used retrospective measures to study the effects of childhood experiences of being bullied on social anxiety in adults, looking at self-blame and style of coping as moderators.…”
Section: A Model Of Bullying and Shamementioning
confidence: 99%
“…One study found that higher levels of bullying in childhood predicted greater social anxiety in later life (Boulton, 2013). Another study found that victimization experiences negatively correlated with three aspects of self-compassion: self-judgment, isolation, and over-identification (Potts & Weidler, 2015), which were correlated with close attachment styles (Beduna, & Perrone-McGovern, 2019). Taking the above evidence into consideration, this study assumes that adolescents who experience bullying will exhibit diminished close attachment and increased anxiety attachment with others.…”
Section: Introductionmentioning
confidence: 99%
“…Self‐compassion has also been implicated in ameliorating the adverse effects of stigma, Internalized‐WS, and/or shame on distress and eating behaviors 23 , 24 , 25 , 26 , 27 including among people with obesity, 9 , 27 , 28 and is associated with less distress in response to dietary lapses and with improved eating behaviors such as intuitive eating. 29 , 30 , 31 , 32 Self‐compassion training is also linked to improvement in eating behaviors and perceived stress, 14 , 32 including via remotely‐delivered treatment, 33 with a recent review suggesting small if promising effects on weight loss.…”
mentioning
confidence: 99%